IMPLEMENTASI PENDIDIKAN KARAKTER DI LINGKUNGAN KAMPUS : STUDI PADA MAHASISWA PAI UIN GUSDUR PEKALONGAN - Hary Setiawan; Abdul Khobir; Muhammad Fadli; Anju Kaila Destianti Tofani; Naila Rif'ah (STKIP Subang, 2026)
ABSTRACT Character education in higher education faces serious challenges due to youth moral degradation and digital disruption that shifts exemplary values. This study aims to describe and analyze the implementation of character education among Islamic Religious Education (PAI) students at K.H. Abdurrahman Wahid State Islamic University (UIN Gusdur) Pekalongan. The method employed is qualitative with a library research approach, supported by content analysis techniques on primary and secondary sources. The results show that the implementation of character education at UIN Gusdur Pekalongan adopts an integrative-holistic model through two main channels: formal curriculum (explicit curriculum) integrating character values in semester learning plans, and hidden curriculum utilizing the campus ecosystem and academic culture. The main values internalized include religious moderation (wasathiyah), tolerance, and academic integrity. Despite facing challenges from post-truth phenomena, echo chambers, and decreased face-to-face interaction, the implementation is optimized through collaborative strategies involving lecturers, study program leaders, and student organizations, as well as authentic evaluation based on behavioral observation and self-reflection portfolios. This study recommends strengthening the role of lecturers as digital mentors and revitalizing physical dialogical spaces to maximize exemplary processes.